Design and Implementation of an Efficient Solar Powered BLDC Motor based Water Pumping System for Pumped Hydro Storage Application - Othman, Muhammad Faris (Universiti Teknologi PETRONAS, 2021)
In this dissertation, design concept prototype will be demonstrated to assure the viability of real design. PV module is used in water pumping system for Pumped Hydro Storage Application using Brushless Direct Current (BLDC) Motor. In this solar fed system, there are two phases. In the first phase, duty ratio of DC-DC boost converter is adjusted to extract full power from the solar Photovoltaic (PV) array. An Incremental Conductance (INC) based Maximum Power Point Tracking (MPPT) control method is used to regulate duty ratio. Boosted Direct Current (DC) voltage is then injected to the solar powered BLDC water pump motor that revert the water from downstream back to the reservoir. The Micro-hydro Water Turbine is used in the second phase in Hydro Pumped Storage Application. At the meantime, the water from reservoir is fed into the Micro-hydro Water Turbine and drive the water back to the downside water source to generate more electricity.